Developing arts-oriented intergenerational learning programs between older adults and young children - Shih, Yi-Huang (Edelweiss Applied Science and Technology, 2024)
Arts-oriented intergenerational learning programs for older adults and young children promote interaction between both groups and cultivate participants’ creativity and aesthetic sense. Body experience and participation in art play pivotal roles in the physical and psychological development of older adults. The literature supports this argument. The body experience of older adults and their regular participation in art can be promoted through developing arts-oriented intergenerational learning programs between older adults and young children. This article conducted a document analysis of the development direction of these programs, which include visual arts creation, music co-creation, storytelling and drama performances, and pottery workshops. The concluding section provides an activity plan. It is hoped that such an exploration can broaden intergenerational learning programs for older adults and young children, and enhance the physical and psychological development of older adults.